Perbandingan Hasil Belajar IPA Siswa Dengan Menggunakan Media Power Point Dan Hasil Belajar IPA Siswa Tanpa Menggunakan Media Power Point (Studi Eksperimen Pada Siswa Kelas V SD Inpres 12/79 Gattareng) - Abd Kadir A; Sudarto Sudarto; Risdawati . (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This study is a true experimental quantitative research design that aims to determine whether or not there is a significant difference in the use of power point learning media on the science learning outcomes of fifth grade students of SD Inpres 12/79 Gattareng. Based on the results of descriptive statistical analysis, the average posttest value for the experimental class was 88.69 with a percentage of 95.2% in the very good category and the average posttest for the control class was 73.75 with a percentage of 42.8% in the good category. Based on the results of inferential statistical analysis shows the tcount value (5.223) is greater (>) the ttable value (2.04227) at the 5% significance level. Thus H_0 is rejected and H_1 is accepted. The results obtained in the study are that there is a significant difference between learning using power point media and learning without using power point media.. This is because the use of power point learning media attracts students attention more and increases students knowledge in understanding science learning materials and can meet all student learning styles.